Anti-Black racism in Canadian health care: a qualitative study of diverse perceptions of racism and racial discrimination among Black adults in Montreal, Quebec - Khandideh K. A. Williams; Shamara Baidoobonso; Aisha Lofters; Jeannie Haggerty; Isabelle Leblanc; Alayne M. Adams (BMC, 2024)
Abstract Background Racism has been shown to impact the health of Black persons through its influence on health care, including its expression through implicit biases in provider training, attitudes, and behaviours. Less is known about the experiences of racism in contexts outside of the USA, and how race and racism interact with other social locations and systems of discrimination to shape Black patients' experiences of racism in health care encounters. To help address this gap, this study examined diverse Black individuals' perceived experiences of, and attitudes towards, anti-Black racism and racial discrimination in Canadian health care, specifically in Montreal, Quebec. Methods This descriptive qualitative study adopted a social constructionist approach. Employing purposive maximal variation and snowball sampling strategies, eligible study participants were: self-identified Black persons aged 18 years and older who lived in Montreal during the COVID-19 pandemic, who could speak English or French, and who were registered with the Quebec medical insurance program. In-depth interviews were conducted, and a Framework Analysis approach guided the systematic exploration and interpretation of data using an intersectionality lens. Results We interviewed 32 participants, the majority of whom were women (59%), university educated (69%), and modestly comfortable financially (41%), but diverse in terms of age (22 to 79 years), country of origin, and self-defined ethnicity. We identified five major themes demonstrating substantial variations in perceived racism in health care that are influenced by unique social locations such as gender identity, age, and immigration history: (1) no perceptions of racism in health care, (2) ambiguous perceptions of racism in health care, (3) perceptions of overt interpersonal racism in health care, (4) perceptions of covert interpersonal racism in health care (including the downplaying of health concerns, stereotyping, and racial microaggressions), and (5) perceptions of systemic racism in health care. Conclusions Perceptions of anti-Black racism and racial discrimination in Canadian health care are complex and may include intra-racial group differences. This study begins to address the dearth of empirical research documenting experiences of anti-Black racism in health care in Quebec, highlighting a continued need for serious consideration of the ways in which racism may manifest in the province, as well as a need for anti-racist advocacy. Advancing racial health equity requires greater sensitivity from providers and decision makers to variations in Black patients' health care experiences, towards ensuring that they have access to high quality and equitable health care services.